Missed nursing care and related factors in Iranian hospitals: A cross‐sectional survey. (20th June 2020) - Chegini, Zahra; Jafari‐Koshki, Tohid; Kheiri, Marzieh; Behforoz, Ali; Aliyari, Saeedeh; Mitra, Udita; Islam, Sheikh Mohammed Shariful
Abstract: Aim: To determine the prevalence of, and reasons for, missed care by nurses and the factors associated with it in Iranian hospitals. Background: Despite providing high‐quality patient care in hospitals, nurses often fail to deliver optimum care, which jeopardizes the safety of patients and increases health care costs. Therefore, identifying missed nursing care is essential if the quality of health services is to be improved. Methods: A cross‐sectional study was conducted among 215 nurses working in the medical–surgical wards of eight public and private hospitals in Tabriz, Iran. The 'MISSCARE' survey tool was used to collect data in relation to the extent of missed care and the related reasons. Logistic regression models were used to assess the association between factors and missed nursing care. Results: Results showed that the mean score of overall missed nursing care was 2.57 and 72.1% of the nurses reported that they missed at least one nursing care item on their last shift. 'Patient discharge planning and teaching', 'emotional support to patient and/or family' and 'attend interdisciplinary care conferences whenever held' were the most common missed items by nurses in Iran. In a 5‐point Likert scale, the most important reasons identified by nurses for missed care were 'human resources', 3.11 (95% CI: 3.03–3.19); 'material resources', 2.7 (95% CI: 2.6–2.8); and 'communication', 2.4 (95% CI: 2.3–2.5), respectively. Missed nursing care was associated with sex (OR for males = 2.83, 95% CI: 1.01–7.89), age (OR = 1.16, 95% CI: 1.01–1.33) and the number of patients under care (OR = 1.11, 95% CI 1.01–1.22). A reverse association was found with the number of patients discharged (OR = 0.89, 95% CI: 0.82–0.96) and satisfaction with teamwork (OR = 0.60, 95% CI: 0.41–0.89). Conclusions: There is a need to identify the factors contributing to the incidence of missed nursing care in hospitals and to develop strategies to address these. Implications for Nursing Management: The results of this study highlighted the importance of addressing missed nursing care in Iranian public and private hospitals. Nursing management should consider improving communication between team members and units. Changes are required regarding task division and payments to the nursing staff. Further research is required to understand the reasons behind missed nursing care, and the development of appropriate policies to address better nursing care in hospitals is recommended.